Safe engine-out landing of a passenger plane under the wind conditions - M. A. Kiselev; S. V. Levitsky; V. A. Podobedov (Научный вестник МГТУ ГА, 2019)
The engine failure, according to the flight safety inspection of the Federal Air Transport Agency, caused 4 of 6 aviation accidents in 2017, including 2 air disasters. In general, from 2001 to 2017, events related to the engine failure became the second most frequent cause of aviation accidents (13% of aviation accidents and 12% of air disasters). The worst consequences are associated with the engine failure at the most difficult and crucial stage of the flight landing. For example, it was the engine failure on the final approach that caused the crash of the L-410UVP-E20 RA-67047 aircraft near the Nelkan airfield on November 15, 2017. The article discusses a limiting situation in some sense – the landing of an aircraft with all failed engines under the wind conditions. The authors have proposed for this situation a methodology of calculating the landing approach of an aircraft under the wind conditions in case of failure of all engines of its power plant to an aerodrome equipped with an outer marker. The key features of such methodology are, firstly, the absence of necessity to link the path to the landmarks in the landing aerodrome area, and, secondly, the simplicity of the synthesis and the implementation of the aircraft control based on the proposed methodology during landing in both manual and director or automatic modes. To calculate the approach using the proposed methodology, the crew only needs to know the following values: the minimum drag airspeed on final approach, the height of the flight over an outer marker before landing and spiral approach leg. The content of the methodology in the article is illustrated by the results of the approach calculation when all of the main engines of the Russian short-medium-range MS-21 aircraft fail under the wind conditions.